2013
DOI: 10.3390/ijerph10115629
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Asbestos Exposure: A Review of Epidemiologic and Exposure Data

Abstract: Inhalation of asbestos resulting from living with and handling the clothing of workers directly exposed to asbestos has been established as a possible contributor to disease. This review evaluates epidemiologic studies of asbestos-related disease or conditions (mesothelioma, lung cancer, and pleural and interstitial abnormalities) among domestically exposed individuals and exposure studies that provide either direct exposure measurements or surrogate measures of asbestos exposure. A meta-analysis of studies pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 80 publications
6
37
0
2
Order By: Relevance
“…Nevertheless, these subjects found difficult to recall the exposure duration, and no quantification of exposure duration/potential exposure level was obtained in this study. In general, non-occupational exposure concentrations are lower than occupational exposure levels [25]. Our finding of low levels of SMRP in participants non-occupationally exposed to asbestos is comparable with other report, which showed that there was no significant elevation of SMRP levels in participants exposed to naturally occurring asbestos compared with subjects without asbestos exposure [26].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, these subjects found difficult to recall the exposure duration, and no quantification of exposure duration/potential exposure level was obtained in this study. In general, non-occupational exposure concentrations are lower than occupational exposure levels [25]. Our finding of low levels of SMRP in participants non-occupationally exposed to asbestos is comparable with other report, which showed that there was no significant elevation of SMRP levels in participants exposed to naturally occurring asbestos compared with subjects without asbestos exposure [26].…”
Section: Discussionsupporting
confidence: 80%
“…According to the categories of non-occupational exposure scenarios as previously defined [25], either household contamination (secondary, para-occupational exposure) or neighborhood exposure was recorded in the present study. The household contamination determined here not only referred to the exposure resulting from asbestos fibers brought into the home through the workers' contaminated clothing [25], but also to the occasional exposure when he/she accompanied with his/her relatives during the period of manufacturing asbestos-related product at household textile workshop. Nevertheless, these subjects found difficult to recall the exposure duration, and no quantification of exposure duration/potential exposure level was obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Domestic exposure to asbestos is a major concern in the Australian Capital Territory (ACT). Between 1968 and 1979, D. Jansen & Co. Pty Ltd and its successor firms -commonly and collectively referred to as 'Mr Fluffy' -insulated homes in the ACT and southern New South Wales (NSW) by blowing crushed (loose-fill), mainly amosite, asbestos into roof spaces.…”
mentioning
confidence: 99%
“…Ülkemizde bildirilen 113 asbest depoziti olup, içerik olarak %65 chrysotile, %39 tremolite ve %1 crocidolitdir [1]. Asbest dünyada ısıtma boruları, izolasyon, su borusu kaplamaları, seramik musluk tutturucuları, zemin, duvar ve tavan kaplamaları, kanalizasyon boruları, fren balataları gibi endüstrinin bir çok alanında kullanılmaktadır [1][2]. Asbest minerali binlerce yıldır insanlar tarafından bilinmekte ve kullanılmaktadır (2].…”
Section: Introductionunclassified